Status of Malnutrition of Children Under Five Years in Institutional School (Research Journal on Multi-disciplinary Issues, 2021)
Simply, bad nutrition is malnutrition. The aim of this study was to assess the condition of malnutrition of students under five years. The study followed descriptive cross-sectional research design. For the study, school was selected purposefully and grade was selected randomly. However, 51 students of LKG were participated in the study and only the data of 43 students (24 boys and 19 girls) were analyzed. Age of the students was identified from the school record. Height measuring tape and weighing machine were used to measure height and weight of students. Data were analyzed manually with the reference to World Health Organization (WHO) growth chart 2006. Mean age, height, and weight of students were respectively 49.53 months, 104.88 cm, and 16.326 kg. No students were found stunted whereas only two girls (4.7%) were found wasted and underweight. The status of malnutrition among less than five years students of institutional school is very low. Parents should be suggested to take care of their daughter’s nutritional status.